Pengaruh Inokulasi Rhizobium-CMA Terhadap Pertumbuhan dan Hasil Dua Varietas Kedelai Pada Tanah Entisol - Utari, Lilik; Isnawan, Bambang Heri; Khusna, Farida (Universitas Muhammadiyah Yogyakarta, 2005)
A research to observe the influence of Rhizobium and Vesicular Arbuscular Mycorrhyzae inoculation on growth and yield of Edamame and Wilis varieties of soybeans in Entisol soil. The research was conducted in the green house of Agriculture Faculty, Muhammadiyah University of Yogyakarta, from June to September 2003. The field experiment was arranged in 4x2 factorial Completely Randomized Design (CRD) with three replications. The first factor was inoculation treatment which contains four levels consisted of: (1) without inoculation; (2) Rhizobium inoculation; (3) VAM inoculation and (4) Rhizobium-VAM inoculation. The second factor was the kind of varieties namely Edamame and Wilis. There were 24 research units which contain 12 polybags of each unit. The result of this research showed that there was no interaction between inoculation treatments and kinds of varieties to all of parameters, except the percentage of mycorrhizae infection. Inoculation of Rhizobium and VAM significantly increased the growth and yield of Wilis variety. The 100 grains weight of Edamame variety was 23.21 g and Wilis variety was 7.49 g. Inoculation of Rhizobium on Wilis variety was more compatible than Edamame. Endogenus VAM application on Edamame variety was more compatible than VAM isolates inoculation.